Analisis Pengetahuan Pasien Diabetes Mellitus Tipe II Dengan Kepatuhan Minum Obat Di Dusun Batu Bangka Kabupaten Sumbawa Tahun 2020 - Abdul Hamid; Iga Maliga; Rafi'ah Rafi'ah (STIKES Karya Husada Kediri, 2022)
Diabetes mellitus is a disease that requires long-term therapy and can cause complications in various organs. Knowledge is an important factor for the formation of good health behavior, including medication adherence. Objective: To get an overview and analyze the correlation between knowledge and medication adherence of type 2 DM patients in Batu Bangka Hamlet, Sumbawa Regency. Methods: An observational study with a cross sectional design was carried out on Type 2 diabetes mellitus (DM) patients in Batu Bangka Hamlet, Sumbawa Regency. Research respondents were 30 people who were selected and participated. Based on the results of the analysis test with chi square, the value of x2 count (11,429) > x2 table (3,841) shows that Ho is rejected and H1 is accepted. This means that there is a relationship between Knowledge and Compliance with Taking Medicines in Dusun Batu Bangka, Sumbawa Regency in 2020. This research is expected to be a reference for the community to increase knowledge and drug compliance to prevent the occurrence of type II DM. Subsequent research is directed to be closer in relation to respondents who have just experienced DM (less than 5 years) with respondents who have long suffered from type II DM so that adherence to them can be more visible. Keywords: Diabetes Mellitus; Knowledge; and Medication Adherence.